Dampak Penghindaran Pajak dan Pajak Tangguhan terhadap Manajemen Laba - Arna Suryani (Universitas Batanghari Jambi, 2022)
Various ways can be done by companies for tax avoidance and deferral, but still within the framework of tax provisions. Management can directly or indirectly do tax avoidance which of course will have an impact on the profits earned. This study conducted test whether tax avoidance and deferred tax affect earnings management. Selected a food and beverage subsector company listed on the Indonesia Stock Exchange. Use of descriptive methods by doing regression, classical hypothesis testing, and hypothesis testing. The result of the study is show tax avoidance in a company is carried out directly and indirectly will affect the profits obtained by management. Companies have a tendency to reduce reported earnings in the context of tax deferral. This research proves that the company always takes various ways to minimize the tax burden. Good governance is needed in order to reduce opportunistic actions of management